TcAMPK: A cellular energy homeostasis hub regulator with unique characteristics in Trypanosoma cruzi - Sternlieb, Tamara (2020)
The AMP-activated protein kinase (AMPK) is a heterotrimeric enzyme involved inmaintaining energy homeostasis in response to different stresses. During the transitionbetween the mammalian host and the insect vector, Trypanosoma cruzi (Chagasdisease), faces different environmental fluctuations, all of which prompt the parasite toremodel its metabolism to adapt and survive. Recently, it was shown that Trypanosomabrucei AMPK is involved in the differentiation process and in surface protein expressionchanges in response to nutritional stress.We identified four genes for the AMPK subunits of T. cruzi (α1 and α2 catalytic subunits,β and γ regulatory subunits). The β and γ subunits are largely conserved in their domainstructure. However, the alpha subunits show significant sequence, structure andevolutionary differences from the human counterparts. The presence of these subunits inT. cruzi epimastigotes was confirmed by several experimental approaches. TcAMPKαsubunits over-expression in epimastigotes showed opposite effects on growth rate. AMPKactivity is also upregulated in epimastigote under starvation. Each of these subunitscould complement the ?glucose dependent? phenotype of S. cerevisiae conditionalmutants lacking SNF1. Starvation assays with AMPKα over-expressing parasites alsoshowed a role of AMPK in autophagy. Our results confirm the presence of a functionalAMPK orthologue in T. cruzi. We also explore the pathways in which TcAMPK may beinvolved using in silico analysis of putative substrates.